Oxide nanoparticle-doped molten carbonate salts for thermal energy storage - Guo, Xiaotong (2020)
An increased percentage of renewable energy is being deployed in the total amount of global energy supply in light of the challenging criteria and scenarios for the reduction of greenhouse gas emissions from using fossil fuels. However, the biggest drawback of renewable energy is the intermittence of energy generation, most of which is quite time-and-climate dependant. As such, various technologies have been pursued to address the issue. Energy storage technology is increasingly accepted as an indispensable and effective approach towards reliable conversion of the unstable and intermittent renewables to a stable, secure and sustainable energy supply. In recent years, the great progress of concentrating/concentrated solar power (CSP) technologies has provided an efficient and sustainable route to reflection and collection of the solar irradiance. Meanwhile, the integration of thermal storage capability with CSP makes it possible to motivate and accelerate the generation of solar thermal electricity (STE) in many regions in the world, specially owing to the flexibility and energy security it can provide to power systems. Rapid development of the thermal energy storage (TES) technology and the successful utilisation of ‘Solar Salt’ in an increasing number of commercial CSP plants in recent decades have encouraged the extensive research on molten salts as TES materials. The thesis considers carbonate-based molten salts as promising candidates of high-temperature sensible TES materials. Different oxide nanoparticles (Al2O3, SiO2 and MgO) were utilised in the molten carbonate salts. For each kind of oxide nanoparticles, a series of salt mixtures were prepared using the static fusing method at different concentrations. Besides, other methods of preparation were employed for comparison to pursue the optimal behaviour of heat capacity enhancement. Thermophysical properties including liquidus temperature, specific heat capacity, and thermal stability were characterised by an assortment of testing devices, primarily DSC and TGA. The results showed that the specific heat capacity of prepared molten salt mixtures was well enhanced by those three nanoparticles. The largest specific heat capacity enhancement of over 30% was obtained by the molten carbonate salt with MgO nanoparticles which was prepared by the in-situ method. At a concentration of 1 wt.%, each type of nanoparticles achieved the largest enhancement. Moreover, all prepared samples were proved to have excellent thermal stability up to 800oC, showing great potentials in serving as the high-temperature TES materials. Besides, extra ex-situ analytical devices, primarily SEM, XRD, EDX were employed to investigate the mechanism of the divergent results of the thermophysical properties, especially the specific heat capacity. Different factors including the size, concentration, morphology, the principle of formation of the nanostructures and the specific heat capacity prediction model were all discussed in detail. These preliminary findings and understanding warrant and encourage more effort to systematically analyse and integrate previous findings and contradictions originated from the scattered methods and techniques applied to facilitate more comparable and repeatable outputs in the further work.